Atomic resolution imaging of beryl: an investigation of the nano‐channel occupation. (3rd November 2016) - ARIVAZHAGAN, V.; SCHMITZ, F.D.; VULLUM, P.E.; VAN HELVOORT, A.T.J.; HOLST, B.
Summary: Beryl in different varieties (emerald, aquamarine, heliodor etc.) displays a wide range of colours that have fascinated humans throughout history. Beryl is a hexagonal cyclo‐silicate (ring‐silicate) with channels going through the crystal along the c ‐axis. The channels are about 0.5 nm in diameter and can be occupied by water and alkali ions. Pure beryl (Be3 Al2 Si6 O18 ) is colourless (variety goshenite). The characteristic colours are believed to be mainly generated through substitutions with metal atoms in the lattice. Which atoms that are substituted is still debated it has been proposed that metal ions may also be enclosed in the channels and that this can also contribute to the crystal colouring. So far spectroscopy studies have not been able to fully answer this. Here we present the first experiments using atomic resolution scanning transmission electron microscope imaging (STEM) to investigate the channel occupation in beryl. We present images of a natural beryl crystal (variety heliodor) from the Bin Thuan Province in Vietnam. The channel occupation can be visualized. Based on the image contrast in combination with ex situ element analysis we suggest that some or all of the atoms that are visible in the channels are Fe ions.